2020
DOI: 10.21037/apm-20-1172
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA elevates serum soluble klotho levels and decreases cardiovascular events in patients on maintenance hemodialysis: a prospective before-after study

Abstract: Background: Cardiovascular disease (CVD) is the most common adverse event of maintenance hemodialysis (MHD), in which serum soluble klotho plays a vital role. Tanshinone IIA (tan) has been used to protect the cardiovascular system for hundreds of years. This study was performed to investigate the effects of tan on klotho level and cardiovascular events of MHD patients.Methods: Totally 112 patients were enrolled in this study, and their demographic, clinical, and laboratory characteristics were collected at adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Ten publications, involving 1,204 participants were eligible according to the inclusion and exclusion criteria (Kitagawa et al, 2013;Buiten et al, 2014;Cai et al, 2015;Di Lullo et al, 2015;Morita et al, 2015;Krishnasamy et al, 2017;Zheng et al, 2018;Koga et al, 2020;Xu et al, 2020;Chen et al, 2021). All included studies had observational or cross-sectional design.…”
Section: Study Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten publications, involving 1,204 participants were eligible according to the inclusion and exclusion criteria (Kitagawa et al, 2013;Buiten et al, 2014;Cai et al, 2015;Di Lullo et al, 2015;Morita et al, 2015;Krishnasamy et al, 2017;Zheng et al, 2018;Koga et al, 2020;Xu et al, 2020;Chen et al, 2021). All included studies had observational or cross-sectional design.…”
Section: Study Featuresmentioning
confidence: 99%
“…Primary features of the included studies and baseline information on participants are shown in Table 1. Among these studies, five reported correlation coefficients (r) pertaining to the association between sKlotho level and VC using Pearson correlation or Spearman correlation analysis (Cai et al, 2015;Di Lullo et al, 2015;Krishnasamy et al, 2017;Zheng et al, 2018;Koga et al, 2020); five reported ORs and CIs pertaining to the association between sKlotho level and VC according to multivariate logistic regression analysis (Cai et al, 2015;Morita et al, 2015;Zheng et al, 2018;Koga et al, 2020;Chen et al, 2021); one study only reported a β-value in multivariate logistic regression analysis (Kitagawa et al, 2013); and two studies reported β-values and CIs pertaining to the association between sKlotho level and VC according to multivariate linear regression analysis (Buiten et al, 2014;Xu et al, 2020). Regarding the correlation between sKlotho and non-VC clinical findings among the included studies, one study reported ORs and CIs pertaining to the association between sKlotho level and vascular dysfunction (Kitagawa et al, 2013) or cardiovascular events (Buiten et al, 2014) according to multivariate logistic regression analysis.…”
Section: Study Featuresmentioning
confidence: 99%
See 3 more Smart Citations